Recent advances of enterovirus 71 $$3{\rm C}^{{\rm pro}}$$ 3 C pro targeting Inhibitors - Rominah Onintsoa Diarimalala; Meichun Hu; Yanhong Wei; Kanghong Hu (Virology Journal, 2020)
Abstract With CA16, enterovirus-71 is the causative agent of hand foot and mouth disease (HFMD) which occurs mostly in children under 5 years-old and responsible of several outbreaks since a decade. Most of the time, HFMD is a mild disease but can progress to severe complications such as meningitis, brain stem encephalitis, acute flaccid paralysis (AFP) and even death; EV71 has been identified in all severe cases. Therefore, it is actually one of the most public health issues that threatens children’s life. $$3{\rm C}^{{\rm pro}}$$ 3 C pro is a protease which plays important functions in EV71 infection. To date, a lot of $$3{\rm C}^{{\rm pro}}$$ 3 C pro inhibitors have been tested but none of them has been approved yet. Therefore, a drug screening is still an utmost importance in order to treat and/or prevent EV71 infections. This work highlights the EV71 life cycle, $$3{\rm C}^{{\rm pro}}$$ 3 C pro functions and $$3{\rm C}^{{\rm pro}}$$ 3 C pro inhibitors recently screened. It permits to well understand all mechanisms about $$3{\rm C}^{{\rm pro}}$$ 3 C pro and consequently allow further development of drugs targeting $$3{\rm C}^{{\rm pro}}$$ 3 C pro . Thus, this review is helpful for screening of more new $$3{\rm C}^{{\rm pro}}$$ 3 C pro inhibitors or for designing analogues of well known $$3{\rm C}^{{\rm pro}}$$ 3 C pro inhibitors in order to improve its antiviral activity.